Volume-Outcome Relationship of Resternotomy Coronary Artery Bypass Grafting - Rappoport, Nadav; Shahian, David M; Galai, Noya; Aviel, Gal; Keaney, Jr, John F; Shapira, Oz M (The Annals of thoracic surgery, 2023)
We assessed volume-outcome relationships of resternotomy coronary artery bypass grafting (CABG). We studied 1,362,218 first-time CABG and 93,985 resternotomy CABG patients reported to The Society of Thoracic Surgeons Adult Cardiac Surgery Database between 2010 and 2019. Primary outcomes were in-hospital mortality and mortality and morbidity (M&M) rates calculated per hospital and per surgeon. Outcomes were compared across 6 total cardiac surgery volume categories. Multivariable generalized linear mixed-effects models were used considering continuous case volume as the main exposure, adjusting for patient characteristics and within-surgeon and hospital variation. We observed a decline in resternotomy CABG unadjusted mortality and M&M from the lowest to the highest case-volume categories (hospital-level mortality, 3.9% ± 0.6% to 3.3% ± 0.1%; M&M, 18.5% ± 1.1% to 15.7% ± 0.4%, P < .001; surgeon-level mortality, 4.1% ± 0.3% to 4.1% ± 1.3%; M&M, 18.5% ± 0.6% to 14.5% ± 2.2%, P < .001). Looking at outcomes vs continuous volume showed that beyond a minimum annual volume (hospital 200-300 cases; surgeon 100-150 cases, approximately), mortality and M&M rates did not further improve. Using individual-level data and adjusting for patient characteristics and clustering within surgeon and hospital, we found higher procedural volume was associated with improved surgeon-level outcomes (mortality adjusted odds ratio, 0.39/100 procedures; 95% CI, 0.24-0.61; M&M adjusted odds ratio, 0.37/100 procedures; 95% CI, 0.28-0.48; P < .001 for both). Hospital-level adjusted volume-outcomes associations were not statistically significant. We observed an inverse relationship between total cardiac case volume and resternotomy CABG outcomes at the surgeon level only, indicating that individual surgeon's experience, rather than institutional volume, is the key determinant.